Efeito de cátions metálicos nas propriedades de filmes poliméricos a base de sericina e álcool polivinílico - Almeida, Karina Fernanda Ribeiro de (2024)
Research and development of new technologies in the area of materials and chemical procedures, seeking new innovations in various fields of technology, such as medicine, has been the focus of many scientific studies that constantly seek innovations. The use of polymeric materials for application in the biomedical area is constantly developing, and they have important applications such as controlled drug release systems, muscle tissue regeneration, cell encapsulation and blends for topical use. In this area, the appli-cation of polymers of natural origin such as Sericin, a protein extracted from the cocoon of the silkworm (Bombyx mori), stands out. The application of Sericin in polymeric films requires the use of plasticizing and/or crosslinking agents in order to produce blends with better properties for their intended purpose. A similar effect was recently observed generated by the introduction of Al3+ cations in polymeric systems. The research in ques-tion focused on evaluating the effects of metal ions on the properties of polymeric films of the Sericin/PVA blend obtained by the casting technique. In this way, polymeric films with different metal ions such as Na+, Mg2+, Al3+, among other convenient ions, were prepared. The films were evaluated for their mechanical, thermal and spectroscopic properties, which made it possible to observe the solubility of the Al3+ ions induced by crosslinking, making the films insoluble and with hydrogel characteristics due to their low solubility. While the films with Na+ and Mg2+ ions remained highly soluble. In me-chanical terms, the films with Al3+ showed greater rigidity due to the crosslinking formed. The films without metal ions, on the other hand, were rigid without any mallea-bility, while the films with Na+ and Mg2+ were more malleable. Thus concluding that the introduction of metal ions affects the conformation of the polymeric structures of the films, improving or decreasing intermolecular interactions. In this way, depending on the ionic radius and valence of these ions, it would be possible to optimize a condition for the production of a material with mechanical properties and the desired profile, such as, for example, more suitable conditions for the release of drugs.